Pengaruh Penerapan Kurikulum Merdeka Belajar Terhadap Hasil Belajar Matematika Ditinjau dari Perbandingan Penerapan Kurikulum 2013 di SD Karya Bakti I Medan - Riani, Nova (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the implementation of the independent learning curriculum in the context of students' mathematics learning outcomes. The type of research used is quantitative with an ex-post facto design. The sample determination technique was carried out by random sampling. Primary data collection is in the form of midterm exam results in mathematics subjects as well as population and research samples, namely class III B students with a total of 33 students. The data was analyzed in a quantitative descriptive manner. The results of the study show that the implementation of the independent learning curriculum is no longer based on themes but subjects that are effective by each teacher based on an agreement on what field of study to be taught, the application of the independent curriculum has begun to be well adopted by students. Based on the results of data analysis, there was a significant difference in the results of the mid-semester exam in the ganji semester (the implementation of the 2013 curriculum) and the results of the mid-semester exam in the even semester (the implementation of the independent learning curriculum) after the paired sample t-test was applied which showed a significant difference in the comparison of mathematics learning outcomes of grade III B students at SD Karya Bakti I Medan.